Absence of Ischemic Injury after Sacrificing the Superior Petrosal Vein during Microvascular Decompression. Issue 3 (19th June 2019) - Xia, Yuanxuan; Kim, Timothy Y; Mashouf, Leila A; Patel, Kisha K; Xu, Risheng; Casaos, Joshua; Choi, John; Kim, Eileen S; Hung, Alice L; Wu, Adela; Garzon-Muvdi, Tomas; Bender, Matthew T; et al.
Abstract: BACKGROUND: Sacrificing the superior petrosal vein (SPV) is controversial during a microvascular decompression (MVD). There have been multiple reports of complications including life-threatening brainstem infarction and cerebellar edema. OBJECTIVE: To analyze the potential for vascular complications when the SPV is sacrificed during an MVD. METHODS: Retrospective chart review was performed to identify all MVDs for trigeminal neuralgia and hemifacial spasm from 2007 to 2018 at 1 institution. Cases with ≥1 mo of follow-up were included and SPV sacrifice was noted. The primary outcome was complications related to SPV sacrifice including sinus thrombosis, cerebellar edema, and midbrain or pontine infarction. Imaging was used to confirm all potential vascular complications noted in medical records. Fisher's exact test and unpaired t -tests were used to compare between groups. RESULTS: A total of 732 MVD cases were identified and 592 met inclusion criteria with an average follow-up of 11.8 ± 16.4 mo and a male-to-female ratio of 1:2.2. The SPV was sacrificed in 217 cases and retained in 375 cases. No SPV-related vascular complications were found in this study. Two unrelated cases of vascular complications were identified and both were in the nonsacrificed group. One case involved cerebellar bleeding while the other was an ipsilateral transverse sinus thrombosis that was present preoperatively. CONCLUSION: In MVDs, there is no difference in the rate of vascular complications when the SPV is sacrificed compared to preserved. To best visualize a cranial nerve and optimize safe decompression, surgeons should feel free to sacrifice the SPV.